Pengaruh Pemberian Kompres Aloe Vera Terhadap Suhu Tubuh Pada Anak Di Wilayah Kerja Puskesmas Kuma Kecamatan Tabukan Tengah Kabupaten Kepulauan Sangihe - Fitriani Edhis; Petronela Mamentu; Rukmini Harun (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Fever is a condition where the body temperature increases from normal limits to a temperature of >38°C. Fever is a sign that body temperature has a process to fight infection, body temperature >37.5°C can be classified as fever which can be caused by auto-immunity and infection (Alwiyah et al, 2019). The aim of this research is to find out whether there is an effect of giving Aloe compresses. Vera on the body temperature of children in the working area of ​​the Kuma Health Center, Central Tabukan District, Sangihe Islands Regency.This research was conducted using a quasi-experimental method with a one group pretest and posttest design. Sampling used accidental sampling technique with 12 subjekts. The intervention was carried out by giving an Aloe Vera compress for 20 minutes, measuring body temperature using a digital thermometer. The data analysis used is the Wilcoxon statistical test.The results of this study showed that there was a decrease in body temperature in the subjekts after the Aloe Vera compress was applied. The results of the analysis using the Wilcoxon test obtained a P value = 0.002 where (a=<0.05).The conclusion of the research is that there is an effect of giving Aloe Vera compresses on body temperature in children in the working area of ​​the Kuma Health Center, Central Tabukan District, Sangihe Islands Regency. It is hoped that parents will gain new knowledge to treat fever in children, not only using pharmacological measures but also using Aloe Vera as initial treatment for children with fever.